The Influence of Price, Service Quality, and Brand Image on Consumers' Purchase Decisions on Mixue Ice Cream & Tea Jl. Mastrip No. 41 Sukomulyo, Lamongan - Cindy Permatasari; Abid Muhtarom; Nurul Bdriyah (Sean Institute, 2024)
This study aims to analyze the influence of price, service quality, and brand image on consumer purchase decisions at Mixue Ice Cream & Tea Jl. Mastrip No. 41 Sukomulyo, Lamongan. The study used a quantitative approach with a Mixue consumer population of 2,762 people during the period from August to October 2023. The number of samples was determined using the Slovin formula with an error rate of 10%, so 96 respondents were obtained. The sampling technique uses simple random sampling. Data were collected through observation, interviews, and Likert scale questionnaires, then analyzed using SPSS version 25 through validity, reliability, classical assumptions, multiple linear regression, multiple correlation, determination coefficient, t-test, and F test. Service quality and brand image have a positive and significant effect on purchasing decisions. Simultaneously, price, service quality, and brand image had a significant effect on purchase decisions with an F value of 30,420 and a significance of 0,000. The R-Square value of 0.498 indicates that 49.8% of the variation in purchasing decisions is explained by all three study variables, while the remaining 50.2% is explained by other factors outside the model. The most dominant variable is brand image.